BARRIERS TO SUSTAINABLE DEVELOPMENT IN FASHION INDUSTRY: SUPPLY CHAIN COMPLEXITY AND CONSUMERS’ ATTITUDE-BEHAVIOR GAP - Starčević, Slađana; Marinković, Veljko; Vjetrov, Ana (International Journal of Economic Practice and Policy, 2024)
Sustainability has become the world’s megatrend. A large number of companies are under pressure of the governments and the public to implement sustainable business practices. Unlike the food industry where demand for sustainable products is relatively easy to achieve because food directly affects the health of consumers, in fashion industry this is not the case. The aim of the paper is to analyze barriers in the development of a sustainable fashion industry, including: complexity of establishing sustainable supply chain, unclear certification and labeling system, high prices of the sustainable fashion products, high growth rate of the fast fashion industry, low consumer awareness of the importance of sustainability in the fashion industry which leads to a gap between consumer attitudes and buying behavior, and low demand for sustainable fashion products. In addition, sustainable fashion is a contradictory term. The whole point of fashion is change of styles from season to season, which in turn accelerates purchases. This is contrary to the concept of sustainable fashion, which implies a slowdown in consumption. Meta-analysis was used as a main method of research in this paper for the purpose of integrating the findings of many studies and directing prospective research.